Performance Evaluation of Ball Mill Type Grinding Machine for Particle Size Reduction of Porang Glucomannan Crystals - Agus Sutejo; Dionisius Dwi Wicaksono; Gatot Pramuhadi (The University of Lampung, 2024)
A wide gap in the price of glucomannan flour and porang tubers leads to develop a machine to process tubers into fine flour with good performance. The purpose of this research was to analyze and determine the performance of a ball mill machine on the flour yield as well as its quality. Research was conducted at PT Daud Teknik Maju Pratama from January – May 2023. Testings were carried out under two treatment factors, namely rotational speed (21.2 and 41.6 rpm) and processing time (0.5 h, 1.0 h, 1.5 h, 2 h). The test was carried out using 150 g sample for each treatment with three replications. The response variables included capacity, percentage of size reduction, material losses, engine power, and flour quality. The results showed that the optimum capacity of the ball mill machine was 12.5 kg/batch. The highest percentage of size reduction was 96.27% and the lowest material loss (3.73%) were obtained at 21.2 rpm for 0.5 h of miling process. Treatment with 41.6 rpm for 2 h produced the best flour quality with moisture content of 11.87% and fine flower yield of 63.97% passing through 100-mesh sieve. The power requirements of electric motors at 21.2 rpm and 41.6 rpm were 0.8063 kW and 0.9101 kW, respectively. The best milling capacity (1.560 g/min) was resulted at rotational speed of 62.27% CS. The ball mill machine showed superior results as compared to a disk mill which was not able to grind the glucomannan crystals up to 100-mesh size.Keywords: Ball mill, Glucomannan flour, Performance test, Porang, Refining.